Antihyperglycemic Activity of Root Bark of Polyalthia longifolia Var. pendula and Aerial Parts of Sida rhombifolia Linn. and Its Relationship with Antioxidant Property - Ghosh, G.; Subudhi, B.B.; Mishra, S.K. (Asian Journal of Chemistry, 2010)
Polyalthia longifolia var. pendula (PL) and Sida rhombifolia Linn. (SR) were detected with free radical (DPPH) scavenging action by thin layer chromatography (TLC). The methanolic extract of Polyalthia longifolia var. pendula and Sida rhombifolia Linn. exhibited better antioxidant activity (IC50: 10.77 and 42 μg/mL) than aqueous extract of Polyalthia longifolia var. pendula and Sida rhombifolia Linn. (IC50: 44.36 and 62.68 μg/mL) in DPPH scavenging assay. All the plant extracts were found with low toxicity (LD50 >3 g/kg). The methanolic extract of Polyalthia longifolia var. pendula and Sida rhombifolia Linn. (200 mg/kg) produced significant reduction in blood glucose level at 2 h (p < 0.05), 4 h (p < 0.01) and 8 h (p < 0.01) in streptozotocin induced diabetic rats. In the oral glucose tolerance test (OGTT), the methanolic extract of Polyalthia longifolia var. pendula and Sida rhombifolia Linn. (200 mg/kg) decreased glycemia at 1 h and the effect persisted until 2 h (p < 0.05) after glucose loading. The antihyperglycemic effect of methanolic extract of Polyalthia longifolia var. pendula and Sida rhombifolia Linn. (200 mg/kg) was significant (p < 0.01). This effect is in agreement with the antioxidant property of the extracts, suggesting contribution of free radical scavenging action.